Organisational Factors and Enterprise Resources Planning System (ERPS) User’s Satisfaction; Study of Tanzania Public Sector - JOHN Yuslida (Communications of International Proceedings, 2021)
This study aims to examine the influence of organisational factors on user satisfaction with enterprise resource planning (ERP) system usage in Tanzanian public sector. Empirical data were collected through a survey questionnaire. The questionnaires were distributed to selected user of ERP system in four organisations of the Tanzanian public sector. 263 respondents were established through stratifies sampling technique. 206 filled and completed questionnaires were collected. The results indicate that user are satisfied with ERP usage when organisation consider factors like business process re-engineering, training, feasibility study, training, and employee involvement in the process of implementing ERP system. However, clear budget found to have no significance in improving user satisfaction with the system.  The research recommends on more researches in this context given low information on user satisfaction with ERP system in public sector to enrich the existing knowledge.
Keywords: Enterprise Resource Planning System; User Satisfaction; Organisational Factors; and Public Sector of Tanzania